RANCANGAN APLIKASI AKUNTANSI DAN PAJAK BERBASIS WEB UNTUK USAHA KECIL DAN MENENGAH - Arie Handoko (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Making the accounting application is to facilitate accountancy. With the online accounting application, it will be helpful for employers or companies to perform the registration and monitoring in real time from anywhere and anytime. Online accounting application is made, features a multi-language, tax invoices and tax deposit letter, the exchange of reports between user, AES security and password protection when downloading files. Based on the results of testing that was done by testing directly to the field, the results obtained in accordance with the criteria of accounting in financial reporting, features have been run properly.